Enhancement of spike and wave discharges by microinjection of bicuculline into the reticular nucleus of rats with absence epilepsy - (:unkn) unknown (ELSEVIER SCI IRELAND LTD, 2002)
The aim of this study was to demonstrate the effect of administration of gamma-aminobutyric acid (GABA)(A) receptor antagonist, bicuculline, into the reticular nucleus of the thalamus (nRt) on spike and wave discharges (SWD) and cardiovascular regulation in conscious rats with genetic absence epilepsy. Rats were instrumented with guide cannulas for drug injection and extradural electrodes for electroencephalogram recording. After a 1 week recovery period, iliac arterial catheters were inserted for direct measurement of blood pressure and heart rate. Administration of bicuculline into the nRt produced increases in spontaneous SWD and failed to alter blood pressure and heart rate. These data suggest that GABA(A) receptors located within the nRt are involved in the incidence of SWD, whereas they do not seem to be involved in cardiovascular regulation of rats with genetic absence epilepsy. (C) 2002 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: bicuculline; absence epilepsy; spike and wave; thalamus; cardiovascular; rat; GABAERGIC INHIBITION; BLOOD-PRESSURE; MECHANISMS; THALAMUS; SEIZURES; VIGILANCE; NEURONS; STRAIN